New Insights into 4-Anilinoquinazolines as Inhibitors of Cardiac Troponin I–Interacting Kinase (TNNi3K) - Christopher R. M. Asquith; Tuomo Laitinen; Carrow I. Wells; Graham J. Tizzard; William J. Zuercher (Molecules, 2020)
We report the synthesis of several related 4-anilinoquinazolines as inhibitors of cardiac troponin I–interacting kinase (TNNi3K). These close structural analogs of 3-((6,7-dimethoxyquinazolin-4-yl)amino)-4-(dimethylamino)-N-methylbenzenesulfonamide (GSK114) provide new understanding of structure–activity relationships between the 4-anilinoquinazoline scaffold and TNNi3K inhibition. Through a small focused library of inhibitors, we observed that the N-methylbenzenesulfonamide was driving the potency in addition to the more traditional quinazoline hinge-binding motif. We also identified a compound devoid of TNNi3K kinase activity due to the addition of a methyl group in the hinge binding region. This compound could serve as a negative control in the study of TNNi3K biology. Small molecule crystal structures of several quinazolines have been solved, supporting observations made about overall conformation and TNNi3K inhibition.